2019
DOI: 10.7759/cureus.5083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Premature Greying of Hair on Socio-cultural Adjustment and Self-esteem among Medical Undergraduates in Foundation University, Islamabad

Abstract: Introduction Greying of hair is an inevitable phenomenon that occurs commonly as a person ages. It usually occurs in the fourth decade regardless of gender but now a days, even people in their early twenties can experience premature greying. The objective of our study was to determine the frequency of premature greying of hair and its impact on the socio-cultural spheres of life and self-esteem of medical students. Methodology It is a descriptive cross-sectional study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Even though no scientific basis for the same could be found, a study conducted by Saad et al found that 44.3% of subjects perceived that lack of self-care in the form of inadequate washing, inadequate oiling of the scalp, or excessive use of cosmetics is a risk factor of PHG. (5) This study showed no relation to PHG with shampoo usage and oil usage frequency debunking the myth. PHG has often been linked to various nutritional deficiencies because of the involvement of certain nutrients in the melanogenesis of hair follicles (e.g.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Even though no scientific basis for the same could be found, a study conducted by Saad et al found that 44.3% of subjects perceived that lack of self-care in the form of inadequate washing, inadequate oiling of the scalp, or excessive use of cosmetics is a risk factor of PHG. (5) This study showed no relation to PHG with shampoo usage and oil usage frequency debunking the myth. PHG has often been linked to various nutritional deficiencies because of the involvement of certain nutrients in the melanogenesis of hair follicles (e.g.…”
Section: Discussionmentioning
confidence: 52%
“…(3) Moreover, since hair has a vital role in people's social and sexual communication, PHG can be distressing, especially for adolescents affecting their socio-cultural spheres of life and, in turn, their mental and social health. (5,6) PHG is a rising concern for children and their parents, making it essential to evaluate its prevalence and predominating risk factors. (1,2) The exact aetiology of PHG remains unknown, but it is considered that it occurs in genetically predisposed people exposed to various socio-clinical factors that increase oxidative stress and damage to melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Tóc bạc sớm cũng là vấn đề về tóc thường gặp. Theo nghiên cứu của Muhammad Saad và cộng sự đã cho thấy rằng những người tóc bạc sớm thường bị chú ý, gây trở ngại trong các hoạt động xã hội [5]. Vấn đề cấp thiết được đặt ra là làm thế nào để giải quyết chúng?…”
Section: đặT Vấn đềunclassified
“…Có thể do sự khác biệt về độ tuổi điều tra, chủng tộc và môi trường sống. Tỷ lệ tóc bạc sớm chiếm 20,1%, thấp hơn so với nghiên cứu Muhammad Saad và cộng sự thực hiện trên sinh viên Y khoa (31,2%) [5]. Sự chênh lệch này có thể do cỡ mẫu của nghiên cứu chúng tôi chưa đủ lớn, đối tượng khảo sát là ngành Y nói chung.…”
Section: Một Số Vấn đề Về Tóc Thường Gặp (Rụng Tóc Gàu Tóc Sớm)unclassified